Assessing Capacities for Local Economic Development in Uganda - Kavuma, Susan; Tibamwenda, Assumpta; Mushemeza, Elijah; Bogere, George; Tamale, Lillian; Semakula, Eugene; Mbabazi, Jonas (ACODE, 2020)
he study sought to address four objectives: (i) analyzing the perspectives of actors at the district and Central Government level on the concept of local economic development; (ii) identifying LED initiatives implemented by districts; (iii) assessing the economic potential of districts, and (iv) evaluating the inclusiveness of LED initiatives. First, the report gives an extensive background to the pursuit of LED in Uganda, including the preliminary steps taken in conceptualizing LED and developing the National LED Policy. It further unravels the perspectives of the actors at the district levels including local government leaders, the private sector, civil society organizations (CSOs), citizen groups and others on LED. It also makes an assessment of the implication of the LED policy on local economic development in the districts covered. From the viewpoints of the stakeholders, the report documents the district goals, targets, and strategies related to economic growth and empowerment existing in the LED interventions, challenges, and solutions commandeered. Second, is the identification of local economic potentials and business opportunities in any district for competitive advantages in economic productivity and resource generation. Factors identified included market access, economic density, urbanization, skills, and local transport connectivity; natural heritage, resource endowments such as, land area, population, natural resources, access to water, and access to electricity. Third, inclusive development is articulated as part of the processes and activities concerned with ensuring that all often marginalized and usually excluded groups such as women, persons with disabilities, youth and refugees are involved in the development processes. This inclusiveness ensures that these groups of people possess economic potential in their unique attributes such as artisan skills. The differential roles of refugees and the host communities in LED communities are also analyzed in this study.
Keywords: Local Economic Development; Capacities; Development